Work engagement among health professionals in public health facilities of Bench-Sheko zone, southwest Ethiopia - Temesgen Ginbeto; Ayal Debie; Demiss Mulatu Geberu; Dereje Alemayehu; Endalkachew Dellie (BMC, 2023)
Abstract Background The level of health professional work engagement affects retention, burnout, job satisfaction, patient satisfaction, and outcomes; however, there is a paucity of evidence that benefit health professional work engagement. Therefore, this study aimed to assess work engagement and associated factors among health professionals at public health facilities in the Bench-Sheko zone in southwest Ethiopia. Methods Facility-based cross-sectional study was conducted among 605 health professionals from 29 March to 29 April 2021. A simple random sampling technique was used to select the participants. Data were collected using a self-administered questionnaire. Linear regression was fitted and those variables with p-value < 0.2 in simple linear regression were entered into multiple linear regression analysis. Unstandardized β-coefficient with 95% CI and p-value < 0.05 were used as the cut of points to determine the factors associated with work engagement. Results Mean score percentage of work engagement was 71.8%. Health center staff (β = 0.31; 95% CI: 0.22, 0.40), married professionals (β = 0.10; 95% CI: 0.005, 0.17), co-worker support (β = 0.06; 95% CI: 0.004, 0.11), role clarity (β = 0.14; 95% CI: 0.07, 0.21), reward (β = 0.10; 95% CI: 0.05, 0.15), resilience (β = 0.14 95%; CI: 0.07, 0.21), self-efficacy (β = 0.24; 95% CI: 0.16, 0.31) and optimism (β = 0.20; 95% CI: 0.15, 0.26) were positively associated with work engagement. On the contrary, cognitive demand (β= -0.06; 95% CI: -0.11, -0.01) was negatively associated with work engagement. Conclusion In this study, health professionals had a moderate level of work engagement. Health facilities shall improve their culture of co-worker support, role clarity, reward, resilience, self-efficacy, and optimism to enhance work engagement. Future researchers shall be done further studies to evaluate the relationship between cognitive demand and work engagement among health professionals.